THE EFFECTIVENESS OF DEVELOPING STUDENTS’ ABILITY IN WRITING ENGLISH POETRY THROUGH HYPNOTIC WIRITNG - Moh. Gholib Wahibullah; Rohmani Nur Indah (Universitas Muria Kudus, 2021)
The small portion of teaching literature, especially poetry writing, which is available in the curriculum (K-13) makes students less able to practice writing poetry. The tenth graders at the National Immersion Senior High School (NISHS) Ponorogo are less able to explore the potential of literature in themselves. This research aims at helping the students by using hypnotic writing approach to improve the students' writing poetry. It employs an experimental research design by comparing the scores of the writing skills after implementing hypnotic writing. The result of the t.test is 6.09, compared with the value of the t.table with the degree of freedom (d.b = N - 1 = 20 - 1 = 19) = 2.09 and the significance level used is 5%. Therefore, it is clear that the value of t.test is higher than t.table (6.09 2.09). The finding shows that the post-test scores improve significantly. It means that the improvement of the ability to write English poetry through hypnotic writing in tenth-grade students at National Immersion Senior High School (NISHS) Ponorogo is effective, and the hypothesis is acceptable. The result of this study is expected to be an alternative in the techniques of writing poetry, especially at senior high school.